1994
DOI: 10.1097/00000658-199406000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved Saphenous Vein Allografts for Below-Knee Lower Extremity Revascularization

Abstract: ObjectiveCryopreserved saphenous vein allografts have been offered as an alternative conduit for bypass in ischemic limbs. The ResultsThere was no significant difference in patency related to site of proximal or distal anastomosis, patency of runoff vessels, use of anticoagulation, age, sex, diabetes, hypertension, smoking, indication, source of graft, or use of multiple segments. Revision was required in six grafts for aneurysmal dilatation. Histologic examination of explanted sections of allografts showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 28 publications
(7 reference statements)
4
47
1
4
Order By: Relevance
“…Preserved vein homografts tolerate repeated puncture by large dialysis needles. Similarly, when satisfactory autologous SVGs are not available, cryopreserved homologous SVGs, either cryopreserved or denatured, can be an alternative conduit to the autologous ones in coronary artery bypass,127 construction of aortopulmonary communication,77 a modified Blalock-Taussig shunt,7879 and complex limb-salvage procedures 128129. Some authors127130131 have suggested that use of such conduits should be limited due to poor patency.…”
Section: Discussionmentioning
confidence: 99%
“…Preserved vein homografts tolerate repeated puncture by large dialysis needles. Similarly, when satisfactory autologous SVGs are not available, cryopreserved homologous SVGs, either cryopreserved or denatured, can be an alternative conduit to the autologous ones in coronary artery bypass,127 construction of aortopulmonary communication,77 a modified Blalock-Taussig shunt,7879 and complex limb-salvage procedures 128129. Some authors127130131 have suggested that use of such conduits should be limited due to poor patency.…”
Section: Discussionmentioning
confidence: 99%
“…In general, clinical use of cryopreserved venous and arterial allografts in lower extremity revascularization has been complicated by lower patency rates, aneurysmal dilatation, higher cost, and increased risk of bloodborne infectious diseases when compared to autogenous vein and prosthetic grafts. [25][26][27] Narayanan et al reported a 100% patency rate at 21 days in a rat model in which 5-mm-long and 1-mmdiameter cryopreserved femoral veins were used as interposition arterial grafts across major histocompatibility barriers without immunosuppression. 28 Similarly, Hirase et al reported a 100% patency rate of replanted rat hind limbs at 3 months utilizing 1.5-cm-long arterial and venous cryopreserved allografts.…”
Section: Cryopreserved Venous and Arterial Allograftsmentioning
confidence: 99%
“…However, insufficient donor tissue and questionable patency rates have limited their application. Cryopreserved saphenous veins have been reported to have poor patency rates and are used only when autologous conduits are not available [Martin et al, 1994;Nataf et al, 1995;Cheng and Slaughter, 2013]. The current options for small-diameter graft substitutes remain limited, particularly when the search is confined to synthetic or biological vessels.…”
Section: Introductionmentioning
confidence: 99%